1996
DOI: 10.1063/1.360845
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study on point defects in buried SiO2 film formed by implantation of oxygen

Abstract: Chemical etch rates in HF solutions as a function of thickness of thermal SiO2 and buried SiO2 formed by oxygen implantationDefects in buried SiO 2 films in Si formed by implantation of oxygen ions were characterized by photoluminescence ͑PL͒ excited by KrF ͑5.0 eV͒ excimer laser and synchrotron radiation. Two PL bands were observed at 4.3 and 2.7 eV. The 4.3 eV band has two PL excitation bands at 5.0 and 7.4 eV, and its decay time is 4.0 ns for the 5.0 eV excitation and 2.4 ns for the 7.4 eV excitation. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…From photoluminescence studies, oxygen deficiency centers (ODCs) 73 have been shown to produce emission bands 4.3 eV above the valence band of SiO 2 . 74,75,76,77 Defects in SiO 2 are also observed in the DUV photoemission spectra of glassy SiO 2 and quartz implanted with metals ions. 78,79 In Fig.…”
Section: Resultsmentioning
confidence: 86%
“…From photoluminescence studies, oxygen deficiency centers (ODCs) 73 have been shown to produce emission bands 4.3 eV above the valence band of SiO 2 . 74,75,76,77 Defects in SiO 2 are also observed in the DUV photoemission spectra of glassy SiO 2 and quartz implanted with metals ions. 78,79 In Fig.…”
Section: Resultsmentioning
confidence: 86%
“…However, similar luminescence has not been observed, as reported in our previous paper. 26 Moreover, as mentioned above, it is more reasonable to assume that PLs ␥ HS and ␥ ZS are intrinsic to their respective silicates, that the dependence of the ratio ͑␥ HS / ␤ HS ͒ on x is fairly similar to that of the ratio ͑␥ ZS / ␤ ZS ͒ is supportive to this assumption.…”
Section: Resultsmentioning
confidence: 91%
“…26 This PL has a very long lifetime of ϳ10 ms and two clear PLE peaks around 5.0 and 7.6 eV. It is clear that the present PLs ␤ HS and ␤ ZS do not have such a slow decay component.…”
Section: Resultsmentioning
confidence: 92%
“…Although ion beam synthesis has been widely reported, [6][7][8] the origin of visible luminescence from ion beam synthesized Si nanocrystals has so far been unclear, primarily due to a lack of distinction between luminescence originating from matrix defects and luminescence originating from nanocrystals. It is well known [9][10][11] that defects in SiO 2 display luminescence at various energies including the visible range, so the interpretation of luminescence spectra without distinction of the contribution from defects can be very misleading.…”
mentioning
confidence: 99%